Risk factors associated with challenging behaviour in people with profound intellectual and multiple disabilities. Issue 6 (4th March 2016) - Poppes, P.; van der Putten, A.J.J.; Post, W.J.; Vlaskamp, C.
Abstract: Background: Several factors that correlate with the onset or continuation of challenging behaviour are mentioned in research. These are factors related to persons with ID, but also to direct support professionals and the context. Although many of these factors seem to affect the onset or continuation of challenging behaviour in people with ID in general, results are often inconclusive and have little focus on people with profound intellectual and multiple disabilities (PIMD). The present study aimed to assess the extent to which known factors related to challenging behaviour are also applicable to a group of 198 people with PIMD. Method: To determine which factors were associated with challenging behaviour, univariate analyses on associations between known risk factors and challenging behaviour were conducted. The associated factors were then subject to a regression analysis to determine the extent to which they explain the prevalence of challenging behaviour and can thus be seen as factors associated with challenging behaviour. Results: The results show that, in particular, factors concerning the personal characteristics of people with PIMD, such as sleeping problems and auditory problems, were related to the variance in mean frequency of challenging behaviour. Only one factor related to the direct support professionals was found: when these professionals had been offered training on the subject of challenging behaviour in people with intellectual disabilities in general, they identified significantly more withdrawn behaviour. We found no contextual factors related to challenging behaviour. Conclusion: These findings are generally consistent with findings reported in other studies, especially concerning the personal characteristics of people with PIMD. Further research should focus on the effects of providing safe auditory environments and appropriate sleep schedules for people with PIMD on the occurrence of challenging behaviour.